Finely-Tuned Bis(imino)pyridylcobalt Complexes Enhance Ethylene Polymerization: The Role of Bulky and Halogen Substituents - Elizabeth Ogbe; Yanping Ma; Yizhou Wang; Jiahao Gao; Yang Sun; Wen-Hua Sun (Molecules)
The bis(imino)pyridylcobalt complexes have been finely tuned through using the aniline derivative bearing a meta-chloro substituent, besides its ortho- and para-di(4-fluorophenyl)methyl and ortho-methyl substituents for the series of 2-[1-(3-chloro-4,6-bis((di(4-fluorophenyl)methyl)-2-methylphenylimino)ethyl]-6-[1-(arylimino)ethyl]pyridylcobalt(II) chlorides (2,6-Me2Ph, Co1; 2,6-Et2Ph, Co2; 2,6-iPr2Ph, Co3; 2,4,6-Me3Ph, Co4; and 2,6-Et2-4-MePh, Co5). The compounds were characterized using elemental analysis, 1H/13C NMR, FT-IR spectroscopy, and the single-crystal X-ray diffraction used in confirming the molecular structures of Co1, Co2, Co4, and Co5. The newly synthesized precatalysts, maintaining steric influences with the addition of an electron-withdrawing meta-chloro group, achieved higher activities along with better thermal stability, and controlled molecular weights of polyethylenes obtained. Upon activation with either MAO or MMAO, all catalysts exhibited remarkable activity for ethylene polymerization, for example, 9.2 × 106 g mol−1 h−1 by Co1 at 70 °C with 30 min and 18.0 × 106 g mol−1 h−1 by Co4 with the first 5 min. Co4 demonstrated exceptionally thermal stability with the peak activity of 8.9 × 106 g mol−1 h−1 at 70 °C and slightly decreased to 7.2 × 106 g mol−1 h−1 at 80 °C, and even maintained an activity of 1.6 × 106 g mol−1 h−1 at 100 °C. More importantly, all resultant polyethylenes were characterized as having vinyl-terminal and high-linear feature along with narrow dispersity; the molecular weights could be adapted in the ranges from 6.4 to 50.0 kg mol−1. In comparison with previous cobalt analogs, the current system performed better thermal stability and polymerization efficiency. Therefore, such robust complex catalysts are potentially considered for the polyethylene industry.